Comparative Analysis of the Nescafe Brand within the RTD iced coffee segment among generation Z in the Czech Republic and Germany - Svatoňová, Nela; Taušer, Josef; Leite, Emilene; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The ready-to-drink (RTD) coffee market is growing rapidly. Given that consumers face busier lifestyles in today’s dynamic world, their preferences are significantly evolving towards greater convenience, making RTD coffee beverages a practical choice for their on-the-go needs. Nescafé, as a globally known coffee brand, targets the largest generation to date, Generation Z, with its RTD iced coffee offering. However, consumers of this generation place emphasis on sustainabil-ity, authenticity and experiences. If a brand does not align with these values and preferences, they will most certainly avoid its products. Currently, there is a lack of studies examining brand perception and awareness within the rapidly growing RTD coffee segment. This study thus aims to explore how the Nescafé brand is perceived within this segment by the target audience, Generation Z, in Czechia and Germany. The primary objective is to identify key similarities and differences in brand perceptions and awareness be-tween these two European markets. The theoretical background of this study thus concentrates on two core areas, including Aaker´s brand equity model and Generation Z itself. Aaker´s model is applied in this study as it offers key dimensions of brand equity, which serve as the foundation for the comparison of brand perception and awareness. These dimensions include brand aware-ness, perceived quality, brand loyalty and brand associations. Based on these four dimensions, ten hypotheses are developed and subsequently tested. Data for testing has been collected through an online questionnaire from a total of 120 Generation Z individuals, with 66 respondents living in Czechia and 54 in Germany. The questionnaire includes questions on both brand recall and recognition, as well as Likert-scale based questions. Statisti-cal tests are performed in IBM SPSS Statistics, including the Chi-Square test and the non-para-metric Mann-Whitney U test.
Additionally, mean ranks are also included for more detailed com-parisons. This thus highlights the use of quantitative research method in this study. The findings have revealed several similarities and differences between Generation Z in the Czech Republic and Germany in terms of their perception and awareness of the Nescafé brand within the RTD iced coffee segment. The similarities include low brand recall, relatively high brand recognition, a similar level of brand loyalty to Nescafé over other brands, and a compara-ble association with authenticity. However, key differences have emerged in the perceived qual-ity, willingness to recommend the Nescafé brand (a loyalty aspect), and associations with sus-tainability and experiences. Key recommendations for Nescafé thus include focusing on digital brand visibility (for both countries), elevating the brand´s perceived quality (especially in Czechia), and actively communicating its sustainability practices (especially in Germany).
Vedoucí práce: Josef Taušer
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses